Comprehensive Phylogenomics of Methylobacterium Reveals Four Evolutionary Distinct Groups and Underappreciated Phyllosphere Diversity. (30th July 2022) - Leducq, Jean-Baptiste; Sneddon, David; Santos, Malia; Condrain-Morel, Domitille; Bourret, Geneviève; Martinez-Gomez, N Cecilia; Lee, Jessica A; Foster, James A; Stolyar, Sergey; Shapiro, B Jesse; Kembel, Steven W; Sullivan, Jack M; et al.
Abstract: Methylobacterium is a group of methylotrophic microbes associated with soil, fresh water, and particularly the phyllosphere, the aerial part of plants that has been well studied in terms of physiology but whose evolutionary history and taxonomy are unclear. Recent work has suggested that Methylobacterium is much more diverse than thought previously, questioning its status as an ecologically and phylogenetically coherent taxonomic genus. However, taxonomic and evolutionary studies of Methylobacterium have mostly been restricted to model species, often isolated from habitats other than the phyllosphere and have yet to utilize comprehensive phylogenomic methods to examine gene trees, gene content, or synteny. By analyzing 189 Methylobacterium genomes from a wide range of habitats, including the phyllosphere, we inferred a robust phylogenetic tree while explicitly accounting for the impact of horizontal gene transfer (HGT). We showed that Methylobacterium contains four evolutionarily distinct groups of bacteria (namely A, B, C, D), characterized by different genome size, GC content, gene content, and genome architecture, revealing the dynamic nature of Methylobacterium genomes. In addition to recovering 59 described species, we identified 45 candidate species, mostly phyllosphere-associated, stressing the significance of plants as a reservoir of Methylobacterium diversity. We inferred an ancient transition from a free-living lifestyle to association with plant roots in Methylobacteriaceae ancestor, followed by phyllosphere association of three of the major groups (A, B, D), whose early branching in Methylobacterium history has been heavily obscured by HGT. Together, our work lays the foundations for a thorough redefinition of Methylobacterium taxonomy, beginning with the abandonment of Methylorubrum .